Manipulating gene translation in plants by CRISPR–Cas9-mediated genome editing of upstream open reading frames - Si, Xiaomin; Zhang, Huawei; Wang, Yanpeng; Chen, Kunling; Gao, Caixia (Nature protocols, 2020)
Gene expression is regulated by multiple processes, and the translation of mRNAs into proteins is an especially critical step. Upstream open reading frames (uORFs) are widespread cis -elements in eukaryotic genes that usually suppress the translation of downstream primary ORFs (pORFs). Here, we describe a protocol for fine-tuning gene translation in plants by editing endogenous uORFs with the CRISPR–Cas9 system. The method we present readily yields transgene-free uorf mutant offspring. We provide detailed protocols for predicting uORFs and testing their effects on downstream pORFs using a dual-luciferase reporter system, designing and constructing single guide RNA (sgRNA)–Cas9 vectors, identifying transgene-free uorf mutants, and finally comparing the mRNA, protein and phenotypic levels of target genes in uorf mutants and controls. Predicting uORFs and confirming their effects in protoplasts takes only 2–3 weeks, and transgene-free mutants with edited target uORFs controlling different levels of pORF translation can be obtained within 4 months. Unlike previous methods, our strategy achieves fine-tuning of gene translation in transgene-free derivatives, which accelerates the analysis of gene function and the improvement of crop traits. In this protocol, the authors describe a method to fine-tune gene expression in plants by editing endogenous upstream ORFs with the CRISPR–Cas9 system to prevent their inhibition of the translation of primary ORFs. This protocol yields transgene-free uorf mutant offspring.